HIV self-testing among young women in rural South Africa: A randomized controlled trial comparing clinic-based HIV testing to the choice of either clinic testing or HIV self-testing with secondary distribution to peers and partners. (April 2020) - Pettifor, Audrey; Lippman, Sheri A.; Kimaru, Linda; Haber, Noah; Mayakayaka, Zola; Selin, Amanda; Twine, Rhian; Gilmore, Hailey; Westreich, Daniel; Mdaka, Brian; Wagner, Ryan; Gomez-Olive, Xavier; et al.
Abstract: Background: HIV testing rates in many hyper-endemic areas are lower than needed to curtail the HIV epidemic. New HIV testing strategies are needed to overcome barriers to traditional clinic based testing; HIV self-testing is one modality that offers promise in reaching individuals who experience barriers to clinic-based testing. Methods: We conducted a randomized control trial among young women ages 18-26 living in rural Mpumalanga, South Africa where they were randomized in a 1:1 allocation to either the: (1) HIV Counseling and Testing (HCT) arm: an invitation to test at one of the 9 local government clinics where free HCT is provided and is standard of care (SOC), or (2) choice arm: choice of either a clinic-based HCT invitation or oral HIV Self-Testing (HIVST) kits. Depending on the arm, participants were also provided either: (1) 4 HCT invitations to provide to peers/partners for HIV testing at one of the 9 local clinics, or (2) 4 HIV self-test kits to provide to peers/partners (thus 5 total HIVST kits or HCT invitations). Young women were asked to return 3 months and 9 months after enrollment to assess testing uptake and invitation or kit distribution to peers and partners and experiences with testing. Peers and partners who were reported by index participants to have received kits/invitations during follow-up visits were also invited to attend a study visit to assess their testing experiences. The trial is registered at clinical trials.gov NCT03162965. Findings: 287 young women were enrolled and randomized, with 146 randomized to the HCT arm and 141 to the choice (HCT or HIVST) arm. Of those randomized to the choice arm, over 95% (n=135) chose the HIV self-testing kit and only 6 individuals chose HCT. At the 3-month follow-up visit, 92% of index participants in the choice arm reported having tested for HIV compared to 43% of participants in the HCT arm, resulting in a significant risk difference of 49% (95% CI 40%, 58%). By 9 months, this difference decreased to a risk difference of 25% (95% CI 17%, 33%) between arms (96% in the choice arm and 72% in the HCT arm). Participants in the choice arm were also more likely to invite peers and partners to test compared to the HCT arm (94% vs. 76% or an average of 4.97 vs 2.79 tests). Few male partners were invited to test by index participants; however, index participants in the choice arm were more likely to have their male partners test than index participants in the HCT arm (RR 2.99, 95% CI 1.45, 6.16). Interpretation: When given a choice between clinic-based HIV testing and HIV oral self-testing, the overwhelming majority of young women chose HIVST. In addition, those offered a choice of HIV testing modality were much more likely to test, distribute test kits to peers and partners, and to have peers and partners who reported testing compared to the HCT arm. Self-testing offers an important opportunity to significantly increase testing rates among young women and their peers and partners compared to clinic-based HCT. Other strategies to reach men with testing are needed. Funding: US National Institutes of Health